Global Initiative for Chronic Obstructive Lung Disease strategy for the diagnosis, management and prevention of chronic obstructive pulmonary disease: An Asia-Pacific perspective - Wan, C.T. (2016)
10.1111/j.1440-1843.2005.00692.x